Efectos de la intensidad y oportunidad de raleo sobre la producción volumétrica de Grevillea robusta A. a los 20 años en el sur de Misiones, Argentina - Keller, Aldo Esteban; Crechi, Ernesto Hector; Knebel, Otto Eduardo; Aquino, Diego Rolando (Facultad de Ciencias Forestales, UNaM. EEA Montecarlo, INTA. Colegio de Ingenieros Forestales de Misiones (Coiform.), 2024)
The objective of this work was to analyze an experiment of thinning modalities with Grevillea robusta A. installed in complete random blocks with 2 levels of intensity and witnesses and 3 levels of opportunity in 3 repetitions. The intensity treatments were defined by the basal area, and characterized in: without thinning (witness) and 20 and 40 % thinning of basal area. The 3 opportunity treatments were defined with thinning at 2, 4 and 6 years’ intervals. There were no statistically significant differences in total volume production between treatments at 20 years, consequence of the application of different intensities of thinning.